The Future of Manufacturing: The Italian Roadmap (Springer Nature, 2024)
This book is an open access publication. This book explores innovation paths for improving the positioning of the manufacturing sector in the international arena. The roadmap is the result of intense work over two years, during which companies, universities, research bodies, and associations came together to build a systemic vision for the themes of research and technological innovation with a medium to long term outlook. The work is based on a collaborative framework whereby top-down analysis of the global development trends and scenarios generating the challenges for manufacturing is integrated with a bottom-up approach that engages the Cluster's members in bringing forward their research needs. The roadmap's proposal is structured along 7 strategic action lines designed to face the challenges from the market such as personalized production, industrial sustainability, valorization of humans in factories, high efficiency, and to seize and develop the opportunities offered by enabling technologies such as innovative production processes, evolving and reconfigurable processes, cybersecurity, AI, and digital platforms.